A silyliumylidene cation stabilized by an amidinate ligand and 4-dimethylaminopyridine - Yeong, Hui-Xian (2013)
The synthesis and reactivity of a silyliumylidene cation stabilized by an amidinate ligand and 4-dimethylaminopyridine (DMAP) are described. The reaction of the amidinate silicon(I) dimer [LSi:]2 (1; L=PhC(NtBu)2) with one equivalent of N-trimethylsilyl-4-dimethylaminopyridinium triflate [4-NMe2C5H4NSiMe3]OTf and two equivalents of DMAP in THF afforded [LSi(DMAP)]OTf (2). The ambiphilic character of 2 is demonstrated from its reactivity. Treatment of 2 with 1 in THF afforded the disilylenylsilylium triflate [L′2(L)Si]OTf (3; L′=LSi:) with the displacement of DMAP. The reaction of 2 with [K{HB(iBu)3}] and elemental sulfur in THF afforded the silylsilylene [LSiSi(H){(NtBu)2C(H)Ph}] (4) and the base-stabilized silanethionium triflate [LSi(S)DMAP]OTf (5), respectively. Compounds 2, 3, and 5 have been characterized by X-ray crystallography.